Effect of Foot Reflexology on Clinical Outcomes of Neonates with Hyperbilirubinemia - Mahdy, Noura M.; Mahdy, Noura M.; Kreem, Hekmat E. Abed El; Mohamed, Nahed T.; Aziz, Safwat M. Abdel (International Journal of Membrane Science and Technology, 2023)
Background and objectives: Neonatal hyperbilirubinemia is the most common reason for admission to Neonatal Intensive Care Unit (NICU) that can progress to critical levels. So, foot reflexology is one of the most widely used treatments and it is effective not only in the treatment of illnesses but also in maintaining health. Objectives: This study aimed to determine the effect of foot reflexology on the clinical outcomes of neonates with hyperbilirubinemia.Methods: A quasi-experimental research design was utilized in this study. The study subjects were 60 neonates with hyperbilirubinemia, recruited from NICU in Assiut University Children’s Hospital. They were selected randomly and divided into two groups: the study group received foot reflexology interventions and the control group received routine care. Two tools were used to collect the necessary data, which included a personal structure questionnaire and neonataloutcomes assessment sheet.Results: On the fifth day, the mean of total serum bilirubin over the study group was 7.89±1.12 mg/dl, and over the control group was 10.55±0.55 mg/dl. According to the mean of the duration of phototherapy and hospital stay, the study group was 3.86±0.86- 6.80±0.88 respectively, but over the control group was 5.33±0.75- 10.40±1.22 respectively.Conclusions: A statistically significant positive correlation between applying foot reflexology interventions and improving clinical outcomes of neonates with hyperbilirubinemia. We recommended that in-service training and education programs for neonatal nurses should be conducted on a regular basis to teach them non-pharmacological strategies such as foot reflexology techniques.